TANTANGAN DAN PELUANG BAHAN AJAR ETNOMATEMATIKA PADA SEKOLAH RAMAH ANAK: ANALISIS BIBLIOMETRIX - Setiyadi, Desi; Sarwi, Sarwi; Sudarmin, Sudarmin; Cahyono, Adi Nur (Universitas Wahid Hasyim Semarang, 2024)
This research aims to analyze the development of mathematics teaching materials in the context of child-friendly schools from 2019 to 2024. As an approach that links mathematical concepts with local culture, ethnomathematics has great potential to support inclusive, contextual, and meaningful learning, especially in elementary schools. This research uses a systematic literature review method with a biometric approach analyzed using OpenRefine, VosViewer, Biblioshiny, and Microsoft Excel. Data were taken from scientific articles published in the Scopus database with a focus on mathematics teaching materials and the concept of child-friendly schools. The analysis process includes the identification of research trends, collaboration among researchers, geographical distribution, and the visualization of relationships between main keywords in the relevant literature. The research results indicate that the topic of ethnomathematics is gaining more attention among academics, but a lack of teacher understanding and limited teaching materials still hinders its application in the field. Adequate teacher training also poses a barrier to the implementation of mathematics in schools. Nevertheless, the analysis results indicate a significant opportunity for further research, especially with the increase in the number of publications in recent years. This recommends close collaboration between educators, curriculum developers, researchers, and local communities to strengthen the implementation of ethnomathematics in creating an inclusive and child-friendly learning environment to improve the quality of primary education in Indonesia.